Intermittent explosive disorder subtypes in the general population: association with comorbidity, impairment and suicidality. (23rd June 2020) - Scott, K. M.; de Vries, Y. A.; Aguilar-Gaxiola, S.; Al-Hamzawi, A.; Alonso, J.; Bromet, E. J.; Bunting, B.; Caldas-de-Almeida, J. M.; Cía, A.; Florescu, S.; Gureje, O.; Hu, C-Y.; et al.
Abstract: Aims: Intermittent explosive disorder (IED) is characterised by impulsive anger attacks that vary greatly across individuals in severity and consequence. Understanding IED subtypes has been limited by lack of large, general population datasets including assessment of IED. Using the 17-country World Mental Health surveys dataset, this study examined whether behavioural subtypes of IED are associated with differing patterns of comorbidity, suicidality and functional impairment. Methods: IED was assessed using the Composite International Diagnostic Interview in the World Mental Health surveys ( n = 45 266). Five behavioural subtypes were created based on type of anger attack. Logistic regression assessed association of these subtypes with lifetime comorbidity, lifetime suicidality and 12-month functional impairment. Results: The lifetime prevalence of IED in all countries was 0.8% (s.e. : 0.0). The two subtypes involving anger attacks that harmed people ('hurt people only' and 'destroy property and hurt people'), collectively comprising 73% of those with IED, were characterised by high rates of externalising comorbid disorders. The remaining three subtypes involving anger attacks that destroyed property only, destroyed property and threatened people, and threatened people only, were characterised by higher rates of internalising than externalising comorbid disorders. Suicidal behaviour did not vary across the five behavioural subtypes but was higher among those with ( v . those without) comorbid disorders, and among those who perpetrated more violent assaults. Conclusions: The most common IED behavioural subtypes in these general population samples are associated with high rates of externalising disorders. This contrasts with the findings from clinical studies of IED, which observe a preponderance of internalising disorder comorbidity. This disparity in findings across population and clinical studies, together with the marked heterogeneity that characterises the diagnostic entity of IED, suggests that it is a disorder that requires much greater research.